Functional Production and Characterization of a Fibrin-Specific Single-Chain Antibody Fragment from Bacillus subtilis: Effects of Molecular Chaperones and a Wall-Bound Protease on Antibody Fragment Production - Wu, Sau-Ching (American Society for Microbiology (ASM), 2002)
To develop an ideal blood clot imaging and targeting agent, a single-chain antibody (SCA) fragment based on a fibrin-specific monoclonal antibody, MH-1, was constructed and produced via secretion from Bacillus subtilis. Through a systematic study involving a series of B. subtilis strains, insufficient intracellular and extracytoplasmic molecular chaperones and high sensitivity to wall-bound protease (WprA) were believed to be the major factors that lead to poor production of MH-1 SCA. Intracellular and extracytoplasmic molecular chaperones apparently act in a sequential manner. The combination of enhanced coproduction of both molecular chaperones and wprA inactivation leads to the development of an engineered B. subtilis strain, WB800HM[pEPP]. This strain allows secretory production of MH-1 SCA at a level of 10 to 15 mg/liter. In contrast, with WB700N (a seven-extracellular-protease-deficient strain) as the host, no MH-1 SCA could be detected in both secreted and cellular fractions. Secreted MH-1 SCA from WB800HM[pMH1, pEPP] could be affinity purified using a protein L matrix. It retains comparable affinity and specificity as the parental MH-1 monoclonal antibody. This expression system can potentially be applied to produce other single-chain antibody fragments, especially those with folding and protease sensitivity problems.